A numerical study of the mixing and stratification alterations in estuaries due to climate change using the potential energy anomaly - Lupiola, Jagoba; Bárcena, Javier F.; García-Alba, Javier; García, Andrés (Frontiers in Marine Science, 2023)
The competition between mixing and stratification in estuaries determines the quality of their waters, living conditions, and uses. These processes occur due to the interaction between tidal and fluvial contributions, which significantly vary depending on the estuarine characteristics. For the study of mixing and stratification alterations in estuaries due to climate change, a new methodology is proposed based on high-resolution 3D hydrodynamic modeling to compute the Potential Energy Anomaly (PEA). Regarding the model scenarios, first, a base case is analyzed with the realistic forcings of the year 2020. Subsequently, the forecasts of anomalies due to climate change for sea conditions (level, temperature, and salinity), atmosphere conditions (precipitation, air temperature, relative humidity, and solar irradiance), and river conditions (flow and temperature) are projected for the year 2020. The selected scenarios to analyze hydrodynamic changes are RCP 4.5 and 8.5 for the years 2050 and 2100. The proposed methodology has been applied to the Suances estuary. Independently of the climate change scenario, the stratification intensity increases and decreases upstream and downstream of the estuary, respectively. These results indicate that unlike the 2020 base scenario, in which the stratification zone has been mainly centered between km 4 and 8, for the new climate change scenarios, the stratification zone will be displaced between km 2 and 8, attenuating its intensity from km 4 onwards. The Suances estuary presents and will present under the considered scenarios a high spatiotemporal variability of the mixing and stratification processes. On the one hand, sea level rise will pull the stratification zones back inland from the estuary. On the other hand, climate change will generate lower precipitations and higher temperatures, decreasing runoff events. This phenomenon will decrease the freshwater input to the estuary and increase the tidal excursion along the estuary, producing a displacement of the river/estuarine front upstream of the areas.